Moderating effect of Board Size on Ownership Structure and Financial Performance of Quoted Consumer firms in Nigeria - Omale Success Sunday; Aneke Charles Amobi; Chidinma Martha Dimgba (Matondang Journal, 2025)
Ownership concentration is the stake of shares held by the shareholders with the controlling interest in a firm. This study examines the Moderating effect of Board Size on Ownership Structure and Financial Performance of Quoted Consumer firms in Nigeria. The population comprised all the 21 quoted consumer goods manufacturing firms in Nigeria while the filtering technique was used to arrive at a sample size of seventeen (17) consumer goods manufacturing firms in Nigeria. The hypotheses were tested using a robust fixed effect regression model after conducting some diagnostics tests. The results shows that share ownership concentration has a significant negative effect on the return on assets of quoted consumer goods manufacturing firms in Nigeria while Further results based on the second model indicate that board size significantly moderates the relationship between share ownership concentration and return on assets of quoted consumer goods manufacturing firms in Nigeria. The study recommends that the board of directors of consumer goods firms should minimize the level of share ownership concentration in their firms to the maximum of 60% to encourage dilution of ownership and enhance the financial performance of their firms in Nigeria.